Methodological challenges for biomechanical approaches in winter sports - Senner, V.; Lehner, S.; Mitternacht, J.; Nusser, M. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Many research questions related to performance or to injury prevention require biomechanical approaches and study plans that provide the best achievable compromise between internal and external validity. This is especially true for winter sport activities like skiing or snowboarding which cannot adequately be reproduced under laboratory conditions. The keynote presentation will illustrate how these methodological challenges have been addressed to answer three research questions related to injury prevention and the development of safety gear in winter sports: (1) the loading of the hip joint at different skiing manoeuvers (to answer the question if skiing is recommendable sport for people with hip replacement), (2) the effectiveness of wrist guards for the prevention of wrist or lower arm fractures in snowboarding (3) the development of algorithms for mechatronic ski bindings with the target to reduce the unchanged high rate of knee injuries